Electrified Postsunrise Ionospheric Perturbations at Millstone Hill. Issue 18 (12th September 2021) - Zhang, Shun‐Rong; Erickson, Philip J.; Gasque, L. C.; Aa, Ercha; Rideout, William; Vierinen, Juha; Goncharenko, Larisa P.; Coster, Anthea J.
Abstract: We provide evidence that midlatitude postsunrise traveling ionospheric disturbances (TIDs) are comprised of electrified waves with an eastward propagation component. The post‐sunrise gravity wave (GW) wind‐induced dynamo action effectively generated periodic meridional polarization electric fields (PEFs), facilitating TID zonal propagation in a similar fashion as GW‐driven neutral perturbations. A combination of near‐simultaneous eastward and upward observations using the Millstone Hill incoherent scatter radar along with 2‐dimensional total electron content maps allowed resolution of TID vertical and horizontal propagation as well as zonal ion drifts V east (meridional PEFs). In multiple observations, V east oscillated in the early morning during periods when TIDs exhibited downward phase progression, 30–60 min period, ∼ 140 m/s eastward speed, and 70 km vertical wavelength. Inside these TIDs, multiple flow vortexes occurred in a vertical‐zonal plane spanning the ionospheric topside and bottomside. Subsequently, PEFs weakened after a few hours as TID horizontal wavefronts rotated clockwise. Plain Language Summary: The solar terminator (ST) provides a repeatable, regulated forcing to the upper atmosphere, exciting thermospheric and ionospheric waves. These waves have zonal propagation components due to the terminator's orientation. Nominally, traveling ionospheric disturbances (TIDs) are considered a manifestation of dynamics produced by propagating thermospheric waves such as gravity waves (GWs). However, GW zonal propagation would be expected to be greatly attenuated in the F region since ions cannot easily move zonally across the meridionally oriented magnetic field. This study provides evidence that midlatitude postsunrise TIDs are electrified waves, due to meridional polarization electric fields (PEFs) embedded in the TIDs. We also identified plasma flow vortexes in a vertical‐zonal plane. Although observed TIDs possess some general GW characteristics, their manifestation is more complex. Particularly, GW wind‐induced dynamo action can generate oscillating PEFs and facilitate TID zonal propagation. Our results imply the importance of electrodynamics in understanding the dynamics of ST‐time ionospheric waves. Observations used the Millstone Hill incoherent scatter radar to measure TIDs and their zonal and vertical propagation, as well as F‐region plasma zonal drifts (driven by PEFs) during TID/GW passage. GNSS data were used to provide 2D TID wave characteristics. Key Points: Postsunrise midlatitude periodic traveling ionospheric disturbances occur, propagating eastward with downward phase progression Periodic polarization electric field in meridional direction was embedded in traveling ionospheric disturbances, large in the morning The electrified ionospheric waves are possibly due to gravity wave wind induced F‐region dynamo effects